2015
DOI: 10.1186/s12864-015-2153-5
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of resistance genes to antibiotics, biocides and metals reveals novel insights into their co-selection potential

Abstract: BackgroundAntibacterial biocides and metals can co-select for antibiotic resistance when bacteria harbour resistance or tolerance genes towards both types of compounds. Despite numerous case studies, systematic and quantitative data on co-occurrence of such genes on plasmids and chromosomes is lacking, as is knowledge on environments and bacterial taxa that tend to carry resistance genes to such compounds. This effectively prevents identification of risk scenarios. Therefore, we aimed to identify general patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
355
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 636 publications
(422 citation statements)
references
References 63 publications
26
355
1
5
Order By: Relevance
“…Among the 23 MRG types detected, Zn, Cu, Ni, Mn and Hg resistance genes accounted for more than half (60%) of the total MRGs retrieved. Generally, the resistance genes for commonly consumed antibiotics and metals are more likely to be present in high abundance, which also has been demonstrated in the previous abundance-based surveys (Li et al, 2015;Pal et al, 2015).…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…Among the 23 MRG types detected, Zn, Cu, Ni, Mn and Hg resistance genes accounted for more than half (60%) of the total MRGs retrieved. Generally, the resistance genes for commonly consumed antibiotics and metals are more likely to be present in high abundance, which also has been demonstrated in the previous abundance-based surveys (Li et al, 2015;Pal et al, 2015).…”
Section: Resultssupporting
confidence: 49%
“…The above observed ARG and MRG abundance profiles within the genome collection, plus previous sporadic studies on coresistance in pathogens (Gillings et al, 2015;Wales and Davies, 2015;Di Cesare et al, 2016;Johnson et al, 2016) and the recently reported abundance correlation in clinically important genera (e.g., Escherichia, Shigella and Klebsiella) (Pal et al, 2015) kindled our interest in thoroughly investigating their possible physical genetic co-occurrence, particularly in humanassociated bacteria. Therefore, two concepts, the incidence of encountering ARGs along the distance from MRGs and their average minimum distance (MetA min ), were used to further evaluate the possible risk associated with ARG and MRG coselection by examining their likeliness of co-occurrence on Figure 1 Presence and absence of ARGs and MRGs in the complete genome collection.…”
Section: Co-occurrence Between Args and Mrgsmentioning
confidence: 99%
“…sulfonamides, betalactams, amphenicols, tetracyclines and aminoglycosides, and certain bacterial taxa comprising many pathogens were particularly prone to carrying both MRGs and ARGs, highlighting the potential clinical consequences of co-selection (Pal et al, 2015). However, the bio-availability should be taken into account concerning the co-selection of heavy metals, because it is the bioavailable fractions of heavy metals that impose selective pressure on microbes.…”
Section: Reduction Of Mrgsmentioning
confidence: 99%
“…It may also contribute to the enhancement of ARGs reduction, and this deserves to be elucidated. The co-occurrence of antibiotic and metal resistance in bacteria has been widely observed (Pal et al, 2015), which is caused by the cross-or co-resistance phenomena. Cross-resistance occurs when the same mechanism reduces the susceptibility to metals and antibiotics simultaneously, and co-resistance occurs when separate resistance genes are situated on the same genetic element (Pal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation